2019
DOI: 10.1007/s00259-019-04635-7
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study on the effect of short-term androgen deprivation therapy on PSMA uptake evaluated with 68Ga-PSMA-11 PET/MRI in men with treatment-naïve prostate cancer

Abstract: Prospective study on the effect of short-term androgen deprivation therapy on PSMA uptake evaluated with 68 Ga-PSMA-11 PET/MRI in men with treatment-naïve prostate cancer Abstract Purpose Based on in vitro studies, it is known that androgen deprivation therapy (ADT) increases prostate-specific membrane antigen (PSMA) expression. Therefore, we hypothesised that ADT improves the performance of PSMA-PET imaging in primary staging of prostate cancer. The purpose of the study was to demonstrate the time course effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 21 publications
1
50
0
1
Order By: Relevance
“… Ferraro et al [ 47 ] 2019 Switzerland Retrospective 65 (51–79) 60 13 ± 13.6 ng/mL Staging None 68Ga-PSMA-11 46 Detection of disease Data from PET are able to select patients who benefit from ePLND. Ettala et al [ 48 ] 2019 Finland Prospective 71 (64–78) 9 52 ng/mL (7–280) Staging ADT 68Ga-PSMA-11 9 Acquisition protocol 68Ga-PSMA is associated with an increase uptake due to ADT administration. The optimal time to acquisition is after 3–4 weeks post-ADT.…”
Section: Resultsmentioning
confidence: 99%
“… Ferraro et al [ 47 ] 2019 Switzerland Retrospective 65 (51–79) 60 13 ± 13.6 ng/mL Staging None 68Ga-PSMA-11 46 Detection of disease Data from PET are able to select patients who benefit from ePLND. Ettala et al [ 48 ] 2019 Finland Prospective 71 (64–78) 9 52 ng/mL (7–280) Staging ADT 68Ga-PSMA-11 9 Acquisition protocol 68Ga-PSMA is associated with an increase uptake due to ADT administration. The optimal time to acquisition is after 3–4 weeks post-ADT.…”
Section: Resultsmentioning
confidence: 99%
“…(91 %) Ettala et al . [ 17 ] 9 pts., prospectively enrolled, start of degarelix (Firmagon®) in HSPC [ 68 Ga]-PSMA-11 (baseline and 3 times post-ADT) Heterogeneous increase in PSMA uptake 3 to 4 weeks post-ADT Start of enzalutamide or abiraterone in CRPC Emmett et al . [ 10 ] Cohort 1 (8 pts.…”
Section: Discussionmentioning
confidence: 99%
“…To date, functional and in vitro studies have shown that ADT can result in a rise of PSMA expression. 64 There are few data in the literature describing the flare phenomenon associated with PSMA PET/CT for the evaluation of treatment response, and future works are warranted.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%